2015
DOI: 10.1186/s12960-015-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Projections of specialist physicians in Mexico: a key element in planning human resources for health

Abstract: Projections are considered a useful tool in the planning of human resources for health. In Mexico, the supply and demand of specialist doctors are clearly disconnected, and decisions must be made to reduce labour market imbalances. Thus, it is critical to produce reliable projections to assess future interactions between supply and demand. Using a service demand approach, projections of the number of specialist physicians required by the three main public institutions were calculated using the following variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
14
0
3
Order By: Relevance
“…18 Entre médicos mexicanos se ha observado que las variaciones entre instituciones son más amplias en las áreas hospitalarias que en las ambulatorias y que la tendencia en las primeras es a la caída secular de la producción medida a través de consultas ambulatorias y cirugías. 19 El mecanismo de pago es uno de los temas más controversiales, pues en muchos de estos países se paga por salario porque administrativamente es la forma más fácil de llevar a cabo esta acción. Sin embargo, está claro que los salarios no generan suficientes incentivos a los trabajadores.…”
unclassified
“…18 Entre médicos mexicanos se ha observado que las variaciones entre instituciones son más amplias en las áreas hospitalarias que en las ambulatorias y que la tendencia en las primeras es a la caída secular de la producción medida a través de consultas ambulatorias y cirugías. 19 El mecanismo de pago es uno de los temas más controversiales, pues en muchos de estos países se paga por salario porque administrativamente es la forma más fácil de llevar a cabo esta acción. Sin embargo, está claro que los salarios no generan suficientes incentivos a los trabajadores.…”
unclassified
“…Of all selected papers, 22 were from the US, 17,24,25,27,28,[31][32][33]36,38,39,[43][44][45][46]49,51,[54][55][56]58,59 5 from Canada, 30,40,52,53,57 4 from Australia, 18,19,26,34 3 from UK, 22,23,48 and 10 from Ireland, Japan, Mexico, Oman, Italy, and Iran. 15,16,20,21,29,35,37,41,42,47,50 A quantitative model had been used in 40 papers to estimate the OB-GYNs requirement, and 5 papers had qualitatively or descriptively investigated the factors affecting the supply and demand of the workforce in this field. The results showed that 28 and 12 papers were related to national and regional studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The amount and type of women's insurance coverage (affecting economic access) [23][24][25][26]28,32,33,39,46,[54][55][56] Changing the level of women's expectations and expectations of women's health services 18,22,28,29,34,40,45,46,53, Geographical accessibility to outpatient and inpatient centers 23,28,30,46,52,55,56, utilization rate parameters Average waiting time for outpatient and inpatient services 18,19,28,46,48,52 Outpatient visits to gynecologists 15,19,20,[22][23][24][25][26][27]32,33,36,[40][41][42][43]46,48,50,51,53,[55][56][57] Per capita hospitalized services related to gynecology 15,18,20,22,…”
Section: The Factors Affecting the Supply Of Ob-gynsmentioning
confidence: 99%
“…Predictology as an important technical discipline, plays an increasingly important role in all walks of life today [20][21]. The 1990-2017 Health Human Resources Data are derived from the 2018 China Health Statistics Yearbook.More people/population ratio method, index smoothing method, gray prediction principle and method to predict the absolute demand of health manpower [22][23][24][25][26][27][28][29]. Kalman and Bucy began to study the uneven process of time series in the early 1960s, but did not form a certain system, prompting researchers to find ways to solve these problems [30][31].…”
Section: Methodsmentioning
confidence: 99%